2012
DOI: 10.1088/2041-8205/749/1/l5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Center-to-Limb Variation in Measured Helioseismic Travel Times and Its Effect on Inferences of Solar Interior Meridional Flows

Abstract: We report on a systematic center-to-limb variation in measured helioseismic travel times, which must be taken into account for an accurate determination of solar interior meridional flows. The systematic variation, found in time-distance helioseismology analysis using SDO/HMI and SDO/AIA observations, is different in both travel-time magnitude and variation trend for different observables. It is not clear what causes this systematic effect. Subtracting the longitude-dependent east-west travel times, obtained a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 33 publications
7
109
0
Order By: Relevance
“…Our analysis, which takes into account the systematic center-to-limb effect that was recently found in the local helioseismology analysis techniques (Zhao et al 2012), gives a two-dimensional cross-section picture of the meridional flow inside the nearly entire solar convection zone, and reveals a double-cell circulation with the equatorward flow located near the middle of the convection zone. In this Letter, we describe our analysis procedure in Section 2, present measurements and inversion results in Section 3, and then discuss these results in Section 4.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our analysis, which takes into account the systematic center-to-limb effect that was recently found in the local helioseismology analysis techniques (Zhao et al 2012), gives a two-dimensional cross-section picture of the meridional flow inside the nearly entire solar convection zone, and reveals a double-cell circulation with the equatorward flow located near the middle of the convection zone. In this Letter, we describe our analysis procedure in Section 2, present measurements and inversion results in Section 3, and then discuss these results in Section 4.…”
Section: Introductionmentioning
confidence: 84%
“…It is not quite clear what causes this systematic effect, and a recent study suggested that it might be partially due to the interactions of acoustic waves with the vertical flows in solar granules (Baldner & Schou 2012). Zhao et al (2012) suggested that this systematic effect should be removed before inverting the measured acoustic travel times for interior meridional flow, and proposed to use the travel-time shifts measured in the east-west direction along the equator as proxies of the systematic effect. Their inversion results, after removal of this effect following their suggested method, showed a reduction of ∼10 m s −1 in the inverted meridional flow speed (Zhao et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Dikpati et al (2010a) argue that the absence of such a highlatitude counter cell through much of solar cycle 23 may account for the relatively deep minimum of 2008-2009 and the delayed onset of solar cycle 24. However, evidence for such a high-latitude counter-cell based on feature tracking and helioseismic inversions has so far been lacking, with the former suggesting that poleward flow may persist all the way to the poles (Rightmire-Upton et al 2012) and the latter being thus far inconclusive (Zhao et al 2012). Further insight into this question should be possible in the coming years, with the availability of longer time series from the Helioseismic Magnetic Imager (HMI) on the Solar Dynamics Observatory (SDO), which has the higher spatial resolution needed to minimize limb effects, and also with the advent of future missions, such as Solar Orbiter, which will have a high-latitude vantage point.…”
Section: Observational Contextmentioning
confidence: 99%
“…Again, this study assumed a steady meridional circulation. In reality, the solar cycle is significantly modulated, and the meridional flow is fluctuating (Ulrich 2010;Basu & Antia 2010;Komm et al 2015), (for more about observations of meridional flow, see Haber et al 2002aHaber et al , 2003Zhao et al 2004Zhao et al , 2012Zhao et al , 2013aŠvanda et al 2007Schad et al 2013;Upton & Hathaway 2014), so the next step of development is to verify the applicability of the method to capture the variability of the modulated activity.…”
Section: Solar Prediction and Data Assimilation Methodsmentioning
confidence: 99%